Augmented Reality untuk Pelatihan Jenis Sambungan Ulir Pipa - Ravi Wiyantoko; Ahmad Hamim Thohari; Muhammad Dzuhri Maarief (Politeknik Negeri Batam, 2021)
The process of extracting oil and gas is carried out by drilling with a depth of more than 200 meters below the surface of the ground, so one steel pipe is needed to run the process. The manufacture of steel pipes for the opening process has special standards, one of which is a long pipe. To reach a depth of 200 meters below the ground level, a pipe connection is needed to reach that height. The method of connecting the pipes is called the Thread Connection Type. This method has more than 20 types of threads to be applied in pipe joints. To facilitate the discussion of the types of threads and their specifications, we need a technology that can be used interactive and mobile learning media to deliver detailed information on the type of thread. The author uses the use of Augmented Reality (AR) technology to be applied as an Android-based training media that can facilitate the existing Connection Thread along with special specifications with 3D visualization. This study aims to measure the validity and practicality of using ISO 25010 (in terms of functional suitability, performance efficiency, portability and usability) of learning media so that it is easier to understand and practical. The study consisted of two parts: 1) Validity by experts (5 experts), 2) Practicality by trainees or employees (16 participants) using the USE Questionnaire instrument. Furthermore, in application development using the Multimedia Development Life Cycle (MDLC) method as its development method. As a result, the application was declared feasible with the results of the percentage of experts Validity of 96% and Practicality by employees of 79%.